THE EDUCATIONAL SYSTEM OF NETHERLAND - Vini Wela Septiana; Zulhendri; Nurhayati; Rusdinal; Azwar Ananda; Nurhizrah Gistituati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This studied aims to know the educational system in Netherland. The research method is literature review or literature study, which contains theories relevant to research problems. The result of the educational system of Netherland that the politics and structure of educational system: the Dutch government through its constitution places freedoms in the education system, namely: (a) freedom to establish educational institutions; (b) organize it; and (c) determine their own religious basis or underlying belief. The structure and type of education: there are three levels of formal Dutch education, namely primary, junior secondary and vocational education, and general high school, vocational academies and universities. The general secondary school structure consists of 4 types of schools, namely: pre-university (VWO, 6 years), vocational level I (MAVO, 4 years), and upper level (HAVO, 5 years), vocational academies, and other types of schools. The education management; The form of the Dutch education system is centralized. The responsibility of the central government lies in matters relating to the organization, funding, inspections, examinations, promotion innovation. The reflection of educational of netherland; role of the education inspectorate is very large in controlling the implementation of education in the Netherlands.